2020
DOI: 10.1038/s41419-020-03015-6
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effect of the BRD4-degrading PROTAC A1874 in human colon cancer cells

Abstract: A1874 is a novel BRD4-degrading proteolysis targeting chimera (PROTAC). In primary colon cancer cells and established HCT116 cells, A1874 potently inhibited cell viability, proliferation, cell cycle progression, as well as cell migration and invasion. The BRD4-degrading PROTAC was able to induce caspase and apoptosis activation in colon cancer cells. Furthermore, A1874-induced degradation of BRD4 protein and downregulated BRD-dependent genes (c-Myc, Bcl-2, and cyclin D1) in colon cancer cells. Significantly, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…BRD4 is degraded by PROTACs to overcome BETi resistance caused by BRD4 stability (114,115) (Figure 2). It has been confirmed that PROTACs can effectively induce the degradation of BRD4 and are more effective than corresponding BRD4 inhibitors in inhibiting the growth of tumor cells and promoting cell apoptosis (116,117).…”
Section: Targeting Brd4 Modification Pathway For Disease Treatmentmentioning
confidence: 93%
“…BRD4 is degraded by PROTACs to overcome BETi resistance caused by BRD4 stability (114,115) (Figure 2). It has been confirmed that PROTACs can effectively induce the degradation of BRD4 and are more effective than corresponding BRD4 inhibitors in inhibiting the growth of tumor cells and promoting cell apoptosis (116,117).…”
Section: Targeting Brd4 Modification Pathway For Disease Treatmentmentioning
confidence: 93%
“…To explore the role of cooperativity in ternary complex formation, the Ciulli group studied PROTAC-induced degradation of the BET protein family (BRD2, BRD3, BRD4) ( 83 ), a protein family extensively studied in the PROTAC field ( 27 , 60 , 73 , 74 , 81 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ). Using SPR and ITC, they found that ternary complexes with positive cooperativity (BRD4 BR2 :PROTAC MZ1:VHL; α = 22) caused more efficient cellular degradation than complexes with negative cooperativity (BRD4 BR2 :PROTAC MP61:VHL; α = 0.2).…”
Section: Hijacking Of the Ups: Protacsmentioning
confidence: 99%
“…Minko[ 82 ] reported a similar anticancer activity of ARV-825 in pancreatic cancer and this activity exhibited in both 2D cell culture and 3D multicellular tumor spheroid models. Additionally, Qin et al [ 83 ] showed that A1874 down-regulated c-MYC, Bcl-2, and cyclin D1 in colon cancer cells and had an anti-colon cancer activity by inhibiting cell proliferation, invasion and migration. Strikingly, A1874 presented to be much more effective than other BET inhibitors including JQ1 and I-BET151.…”
Section: New Bet Inhibitors Using Protac Technologymentioning
confidence: 99%